2019
DOI: 10.4038/jnsfsr.v47i1.8928
|View full text |Cite
|
Sign up to set email alerts
|

Varietal diversity of Sri Lankan traditional rice based on sensitivity to temperature and photoperiod at vegetative stage

Abstract: Photoperiod and temperature are two important environmental factors affecting vegetative growth and yield of rice. The varietal diversity based on the response to temperature and photoperiod during vegetative growth was determined in a core collection of 40 Sri Lankan traditional rice accessions (SLTRA) and 2 improved and 2 wild rice types in terms of days were imposed during 2 trials of high temperature (HT) and low temperature (LT) at under. Average DFL of the collection while photoperiod alone affected 1 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…It has been reported that traditional rice cultivars from tropical regions are photoperiod sensitive and require between 160-170 days to mature (Vergara & Chang,1985;Viraktamath, 2013;Nandini, 2020;Khotasena et al, 2022). Most of the studies on photoperiodism of traditional rice in the tropics are from Cambodia (Makara et al, 2001;Tsubo et al, 2009;Uch et al, 2023), Thailand (Cha-um & Kirdmanee, 2007;Boling et al, 2011;Sujariya et al, 2023), and Sri Lanka (Mapalana, 2017;Padukkage et al, 2017;Rathnathunga et al, 2019). The geographical locations of these countries are within 7.9 °N-15.9 °N latitude, thus experiencing different changes in day length throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that traditional rice cultivars from tropical regions are photoperiod sensitive and require between 160-170 days to mature (Vergara & Chang,1985;Viraktamath, 2013;Nandini, 2020;Khotasena et al, 2022). Most of the studies on photoperiodism of traditional rice in the tropics are from Cambodia (Makara et al, 2001;Tsubo et al, 2009;Uch et al, 2023), Thailand (Cha-um & Kirdmanee, 2007;Boling et al, 2011;Sujariya et al, 2023), and Sri Lanka (Mapalana, 2017;Padukkage et al, 2017;Rathnathunga et al, 2019). The geographical locations of these countries are within 7.9 °N-15.9 °N latitude, thus experiencing different changes in day length throughout the year.…”
Section: Introductionmentioning
confidence: 99%